2001
DOI: 10.1044/1092-4388(2001/082)
|View full text |Cite
|
Sign up to set email alerts
|

Speech Motor Stability in IPD

Abstract: Increasing phonatory effort, an integral component of the Lee Silverman Voice Treatment, LSVT, has been identified as an effective management strategy for adults with hypokinetic dysarthria associated with Parkinsonism. The present study compares the effects of increased loudness on lower lip movements to those of changes in speaking rate, another approach to the treatment of hypokinetic dysarthria. Movements of the lower lip/jaw during speech were recorded from 8 adults with IPD, 8 healthy aged adults, and 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(15 citation statements)
references
References 32 publications
0
14
1
Order By: Relevance
“…Since the early 1930’s, it has been claimed that stuttering has its origin in the central nervous system. One of the most consistent findings observed in persons who stutter (PWS) is an anomalous control of the articulatory, laryngeal and respiratory system, mainly due to a timing and coordination deficit (McClean and Runyan, 2000 ; Kleinow et al, 2001 ; McClean et al, 2004 ; Max and Gracco, 2005 ; Loucks and De Nil, 2006 ; Loucks et al, 2007 ). It has become clear that stuttering is not an isolated phenomenon, but rather an element of a more generalized motor timing deficit, as demonstrated in non-speech related movements like finger flexion (Borden, 1983 ), finger tapping (Smits-Bandstra et al, 2006 ) and finger movement sequencing (Forster and Webster, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since the early 1930’s, it has been claimed that stuttering has its origin in the central nervous system. One of the most consistent findings observed in persons who stutter (PWS) is an anomalous control of the articulatory, laryngeal and respiratory system, mainly due to a timing and coordination deficit (McClean and Runyan, 2000 ; Kleinow et al, 2001 ; McClean et al, 2004 ; Max and Gracco, 2005 ; Loucks and De Nil, 2006 ; Loucks et al, 2007 ). It has become clear that stuttering is not an isolated phenomenon, but rather an element of a more generalized motor timing deficit, as demonstrated in non-speech related movements like finger flexion (Borden, 1983 ), finger tapping (Smits-Bandstra et al, 2006 ) and finger movement sequencing (Forster and Webster, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…Decreases in speaking rate may represent a compensatory mechanism in order to maintain accuracy as difficulty increases. Relatedly, but conversely, it has been demonstrated that accuracy and intelligibility decline at markedly increased speaking rates in normal speakers [ 65 , 66 ]. Articulatory difficulty may also be useful for explaining certain speech phenomena on its own.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, STI index may also be used for assessing the effectiveness of treatment of such problems. Kleinow et al reported reductions in STI in response to a speech treatment for adults with hypokinetic dysarthria associated with Parkinsonism [40]. We may potentially apply this approach to the assessment of intervention designed for children with mild CP.…”
Section: Discussionmentioning
confidence: 99%